2020
DOI: 10.3390/ani10060930
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Stimulates Fatty Acid Synthesis Mainly via PLC-γ1/Akt Signaling Pathway in Dairy Goat Mammary Epithelial Cells

Abstract: EGF acts as a ligand of the EGF receptor (EGFR) to activate the EGFR-mediated signaling pathways and is involved in the regulation of cell physiology. However, the roles of EGFR mediated signaling pathways in the regulation of lipid metabolism in goat mammary epithelial cells (GMECs) are poorly understood. To evaluate the impact of EGF on GMECs, the triglyceride (TG) content and lipid droplet were detected, using TG assay and immunofluorescence. Further, expression of lipogenic genes, the protein kinase B (Akt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Several genes have been reported to be involved in ruminant milk fat synthesis, including EGFR, ACSS2, ACSL4, PANK3, DGAT2, and SP1. Among these, EGFR plays an important role in the de novo synthesis of fatty acids in mammary epithelial cells by phosphorylating PLC-γ1 and Akt signaling pathways, inducing adipogenesis-related gene expression and increasing intracellular TG content (Huang et al, 2020). ACSS2 (acyl-CoA synthase short-chain family member 2) performs lipogenesis by synthesizing acetyl-CoA from acetate, which is directly regulated by SREBP1 and plays an important role in ruminant milk fat synthesis (Mu et al, 2021).…”
Section: Candidate Genes Associated With Milk Fatmentioning
confidence: 99%
“…Several genes have been reported to be involved in ruminant milk fat synthesis, including EGFR, ACSS2, ACSL4, PANK3, DGAT2, and SP1. Among these, EGFR plays an important role in the de novo synthesis of fatty acids in mammary epithelial cells by phosphorylating PLC-γ1 and Akt signaling pathways, inducing adipogenesis-related gene expression and increasing intracellular TG content (Huang et al, 2020). ACSS2 (acyl-CoA synthase short-chain family member 2) performs lipogenesis by synthesizing acetyl-CoA from acetate, which is directly regulated by SREBP1 and plays an important role in ruminant milk fat synthesis (Mu et al, 2021).…”
Section: Candidate Genes Associated With Milk Fatmentioning
confidence: 99%
“…This indicates that ELOVL6 not only regulates the elongation of fatty acid chains but also plays an active role in the de novo synthesis of FA and TAG. EGFR has a positive regulatory effect on the de novo synthesis of FA in goat mammary epithelial cells (FASN and ACACA), which is mainly mediated by the AKT and PLC-γ-1 signaling pathways [32]. Therefore, after interfering with the PI4K2A gene, the expression of ELOVL6 and EGFR were downregulated, indicates that PI4K2A may indirectly inhibit the synthesis of milk fat in cows.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that EGFR promotes adhesion between mammary gland cells and regulates the growth and differentiation of human mammary epithelial cells ( Mukhopadhyay et al, 2013 ). EGFR , at concentrations ranging from 12.5 to 50 ng/ml, facilitates the proliferation of mammary epithelial cells in dairy goats, and activation of the EGFR-mediated signaling pathway promotes the survival of mammary epithelial cells in dairy goats ( Huang et al, 2020 ). Therefore, the data obtained in this study provide a basis for future studies on the role of m 6 A methylation in the development of mammary glands in dairy goats.…”
Section: Discussionmentioning
confidence: 99%